Guidelines on Vaccinations in Paediatric Haematology and Oncology Patients. (29th April 2014) - Cesaro, Simone; Giacchino, Mareva; Fioredda, Francesca; Barone, Angelica; Battisti, Laura; Bezzio, Stefania; Frenos, Stefano; De Santis, Raffaella; Livadiotti, Susanna; Marinello, Serena; Zanazzo, Andrea Giulio; Caselli, Désirée
Abstract : Objective. Vaccinations are the most important tool to prevent infectious diseases. Chemotherapy-induced immune depression may impact the efficacy of vaccinations in children. Patients and Methods . A panel of experts of the supportive care working group of the Italian Association Paediatric Haematology Oncology (AIEOP) addressed this issue by guidelines on vaccinations in paediatric cancer patients. The literature published between 1980 and 2013 was reviewed. Results and Conclusion . During intensive chemotherapy, vaccination turned out to be effective for hepatitis A and B, whilst vaccinations with toxoid, protein subunits, or bacterial antigens should be postponed to the less intensive phases, to achieve an adequate immune response. Apart from varicella, the administration of live-attenuated-virus vaccines is not recommended during this phase. Family members should remain on recommended vaccination schedules, including toxoid, inactivated vaccine (also poliomyelitis), and live-attenuated vaccines (varicella, measles, mumps, and rubella). By the time of completion of chemotherapy, insufficient serum antibody levels for vaccine-preventable diseases have been reported, while immunological memory appears to be preserved. Once immunological recovery is completed, usually after 6 months, response to booster or vaccination is generally good and allows patients to be protected and also to contribute to herd immunity.